Pengaruh Self-Efficacy, Lingkungan Kerja Dan Dukungan Atasan Terhadap Transfer Pelatihan Pada Karyawan Bank Pembangunan Daerah (BPD) Bali Cabang Renon - Kimbal, Deby Aneke; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 4 No 11 (2015), 2015)
The training program has an ultimate purpose that is the knowledge obtained in the training can be transferred back into the job. The training transfer becomes something that should be noticed, considering that training transfer identifies to what extent the trainees can apply what they obtain from the training so that it was able to change the attitude of the trainees in performing their jobs. This research aims to find out the impact of self-efficacy, work environment and support from the superior toward the training transfer on the employees of Regional Development Bank (BPD) of Bali at Renon Branch. The sample which is being used consists of 52 respondents by using Simple Random Sampling method. Data analysis technique which is being used is analysis technique of multiple linear regression. The result of research shows that variables of self-efficacy, work environment and support from the superior have a positive impact toward training transfer on the employees of Regional Development Bank (BPD) of Bali at Renon Branch. The variable of support from the superior is a positive variable which influencing training transfer on the employees of Regional Development Bank (BPD) of Bali at Renon Branch.
Keywords: self-efficacy; lingkungan kerja; dukungan atasan; transfer pelatihan